2013
DOI: 10.1007/s11244-013-9941-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Gaseous Urea by FT-IR Spectroscopy and Its Application in Catalytic Urea Thermolysis

Abstract: An analysis method was developed for the quantification of gaseous urea in model exhaust gases by FT-IR spectroscopy. The method was applied for the investigation of the catalytic thermolysis of urea, which is used as ammonia storage compound in the selective catalytic reduction of NO x in diesel engines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…The materials were washcoated on cordierite monoliths (~2.5 g L -1 ) and tested in a dedicated setup under spray conditions [30]. The gaseous reaction products at the reactor outlet were quantified by FTIR spectroscopy (Antaris, Thermo Nicolet gas cell) [6]. The total flow rate was set at 750 L h -1 , and the contact time was varied by changing the number of monolith pieces stacked along the length of the reactor while keeping constant the total catalyst concentration per unit volume.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The materials were washcoated on cordierite monoliths (~2.5 g L -1 ) and tested in a dedicated setup under spray conditions [30]. The gaseous reaction products at the reactor outlet were quantified by FTIR spectroscopy (Antaris, Thermo Nicolet gas cell) [6]. The total flow rate was set at 750 L h -1 , and the contact time was varied by changing the number of monolith pieces stacked along the length of the reactor while keeping constant the total catalyst concentration per unit volume.…”
Section: Methodsmentioning
confidence: 99%
“…However, the application of urea is, in practice, impeded by several problems [3,4]. Alternative ammonia precursors, such as concentrated guanidinium formate, ammonium formate (AmFo), and methanamide solutions, have been proposed to replace urea because they are more thermally stable, freeze at lower temperatures, have a higher ammonia storage capacity, and decompose more selectively [4][5][6][7]. These precursors undergo thermolysis in the hot exhaust to produce formic acid in the gas phase [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bernhard et al. confirmed the presence of these lower frequency bands and they attributed the band around 1560 cm −1 to the asymmetric Ti−OCN−Ti stretching mode of adsorbed urea on titania . However, in contrast with these results, no peaks at higher wavenumbers were detected in our analysis and, moreover, no N 1s peak was revealed in the XPS data in the BE region around 400 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Bernhard et al [37] reported catalytic urea thermolysis as well as hydrolysis under steady-state conditions [42,56]. Figures 16.3 and 16.4 show a catalyst screening, using the data of Ref.…”
Section: Catalytic Urea Decompositionmentioning
confidence: 97%
“…Urea sublimation under vacuum has been known for decades and gaseous urea exists in monomolecular form [32,40,41]. Recent studies have shown that gaseous urea also exists in monomolecular form under atmospheric pressure and that diluted urea vapor is sufficiently stable to be measured by Fourier transform infrared (FTIR) spectroscopy in a gas cell heated to 180°C [39,42]. Comparing the saturation vapor pressure of urea [39,40] with raw NO x emissions of 200-300 ppm of a modern Diesel engine [14] reveals that a temperature of only about 120°C is sufficient for complete evaporation of the required urea (assuming quantitative urea decomposition and NO x reduction).…”
Section: Urea Thermolysis and Evaporationmentioning
confidence: 99%